Study On The Multi-Project Management Practices for Complex Investments - Mircea Sandru; Ionela Carmen Pirnea; Anca Purcarea; Ioana Surugiu; Jochen Schmid (Amfiteatru Economic Journal, 2015)
This paper highlights the results of a study carried out during the doctoral research in case of multi project Engineering, Procurement, Construction, Commissioning (EPCC) investment types. The objective of this study was to improve the project portfolio management. The methodology used in the research presented in this paper is focused on the analysis of the authors related to the approaches debated in literature and theirs applicability in EPCC type investment programs. In this sense were analyzed 11 international projects in petrochemical and refinery field and also 7 investments in other different areas of chemical industry. The research highlighted that the management process of these investments can be improved trough the correct project integration, being able to provide a performing working environment able to sustain the management team in identifying the investment program criticalities and congestion points in order to be able to manage them in an efficient manner in order to assure the reach of the investment goal. Having as consequence the possibility to significant reduction of execution period, up to 16% and in the mean time also the delays related risks through a more efficient investment managerial act.
Keywords: M1; 330; Multi Project Portfolio Management; Efficiency of Portofolio Management; Critical Path; Integrated Master Schedule